2023
DOI: 10.2340/jrm.v55.3497
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Long-Term Cognitive Impairments in Survivors after Cardiac Arrest: A Systematic Review

Abstract: Objective: International guidelines recommend early screening for identification of patients who are at risk of long-term cognitive impairments after cardiac arrest. However, information about predictors is not provided. A systematic review of the literature was performed to identify early predictors of long-term cognitive outcome after cardiac arrest.Methods: Scopus and PubMed were systematically searched to identify studies on early predictors of long-term cognitive outcome in patients after cardiac arrest. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A comprehensive analysis of studies conducted in Europe, China, and the USA showed that the average age of patients who suffered cardiac arrest was 60-66 years, and 58-81% of them were men [3][4][5]. However, rates of mortality, depression, anxiety, and cognitive impairment were higher in women than in men [6,7]. The incidence of cardiac arrest worldwide exceeds 3.7 million annually [8,9].…”
Section: Cardiac Arrestmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive analysis of studies conducted in Europe, China, and the USA showed that the average age of patients who suffered cardiac arrest was 60-66 years, and 58-81% of them were men [3][4][5]. However, rates of mortality, depression, anxiety, and cognitive impairment were higher in women than in men [6,7]. The incidence of cardiac arrest worldwide exceeds 3.7 million annually [8,9].…”
Section: Cardiac Arrestmentioning
confidence: 99%
“…Cognitive problems develop in 42-50% of patients who survive cardiac arrest up to several years after discharge from hospital [13,59]. Other studies have reported that in people who survived cardiac arrest, 50-100% of them experienced cognitive, mood, and functioning disorders [6,7,60]. Even among patients who returned to good neurological condition after discharge from the hospital, 29% experienced memory problems (short-term memory and spatial or contextual memory) and 43% experienced cognitive impairment [28,59].…”
Section: Cognitive Deficits After Cardiac Arrestmentioning
confidence: 99%
“…S100B levels in biological fluids constitute a recognized clinical parameter to evaluate patients with acute brain injury [52][53][54][55][56][57][58][59][60], and a special emphasis has been recently placed on mild traumatic brain injury [61][62][63][64][65][66][67][68][69][70][71] since S100B levels have been proposed as a reliable screening tool in this pathological condition. S100B levels in human brain tissue and their direct correlation with S100B in biological fluids are difficult to evaluate.…”
Section: S100b In Traumatic and Vascular Acute Neural Injurymentioning
confidence: 99%